2003
DOI: 10.1111/j.1752-1688.2003.tb03674.x
|View full text |Cite
|
Sign up to set email alerts
|

IMPACT ASSESSMENT MODEL FOR CLEAR WATER FISHES EXPOSED TO EXCESSIVELY CLOUDY WATER1

Abstract: A new type of empirical model described here enables real time assessment of impacts caused by excessive water cloudiness as a function of (a) reduced visual clarity (excessive cloudiness) and (b) duration of exposure to cloudy conditions, in fisheries or fish life stages adapted to life in clear water ecosystems. This model takes the familiar form used in earlier suspended sediment dose effect models where z is severity of ill effect (SEV), x is duration of exposure (h), y is black disk sighting range (y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 36 publications
0
30
0
1
Order By: Relevance
“…Salmonids in particular may be adversely affected at several life stages in freshwater (Newcombe and MacDonald, 1991;Newcombe and Jensen, 1996;Henley et al, 2000;Newcombe, 2003), although White and Harvey (2007) found that in some cases, adaptive feeding strategies used by trout may overcome difficulties in finding food in turbid conditions. Klein et al (2008, Part B) detailed the linkages between harvest rates, elevated chronic turbidity, reduced growth of juvenile salmonids, and impaired spawning escapement.…”
Section: Introductionmentioning
confidence: 97%
“…Salmonids in particular may be adversely affected at several life stages in freshwater (Newcombe and MacDonald, 1991;Newcombe and Jensen, 1996;Henley et al, 2000;Newcombe, 2003), although White and Harvey (2007) found that in some cases, adaptive feeding strategies used by trout may overcome difficulties in finding food in turbid conditions. Klein et al (2008, Part B) detailed the linkages between harvest rates, elevated chronic turbidity, reduced growth of juvenile salmonids, and impaired spawning escapement.…”
Section: Introductionmentioning
confidence: 97%
“…The presence of a zone of high turbidity near the bottom (nepheloid zone) forced by tides, currents, waves and bioturbation (Cacchione & Drake 1986, Graf & Rosenberg 1997, Pilskaln et al 1998, Palanques et al 2001) may have adapted fish to elevated suspensoid loads, but under such conditions concentrations will usually be much lower than those recorded immediately after trawling. Models have been developed for assessing ill-effects related to sediment doses for lotic, lentic and estuarine species (Newcombe & MacDonald 1991, Newcombe & Jensen 1996, Newcombe 2003. However, the predicted responses had a poor fit to the responses registered in our data.…”
Section: Discussionmentioning
confidence: 60%
“…It was also well below that for most other fish species reviewed by Newcombe & MacDonald (1991) but not other genera of smelt. Newcombe (2000) produced an index that combines both the concentration and duration of SS that kill fish. The high value for North American smelt (Osmeridae, 11.3) indicates that both the Osmeridae and Retropinnidae are more sensitive to high levels of suspended solids than other fish taxa.…”
Section: Figmentioning
confidence: 99%